EFEK PENYUNTIKAN HORMON PREGNANT MARE’S SERUM GONADOTROPIN (PMSG) TERHADAP PENINGKATAN PRODUKTIVITAS INDUK BABI PADA PETERNAKAN BABI KOMERSIL DI KABUPATEN KUPANG - Marianus Perada Kuslianto; Cynthia D. Gaina; Yohanes T. R. M. R. Simarmata (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Pigs are one of the potential livestock to breed with the aim of meeting the needs of animal protein, but in fact the level of pig production is not optimal due to the low efficiency of reproduction. One way that can be used to increase the productivity of sows that by superovulation method. This study aimed to determine the effects of PMSG hormone injections to increase the productivity level of sows that given superovulation treatment. 10 sows that have been selected, be divided into two research groups: control group and treatment group. Before the treatment is given in the form of PMSG hormone injections, sows from both study groups, first injected with hormones PGF2α to estrus synchronization purposes. Then, sows in the treatment group are injected by PMSG hormone with the dose of 2 ml/sow before naturally mating with the boar. After the mating process, the gestation period of pregnant sow will be observed until the parturition time. The parameters were litter size and the birth weight of piglets produced from each sows of the two study groups. Sows were injected with PMSG hormone before mating show better productivity levels compared with sows in the control group. Sows were injected with PMSG hormone produce the overall number of piglets are 46 piglets or the litter size are 9 piglets with the average birth weight of 1.20 kg, while in the control group generates total number of piglets are 36 piglets or the number of litter size are 7 piglets with the average birth weight of 1.05kg. Based on statistical tests, the results showed that there’s no significantly different ((P>0.05) for the litter size of each research groups. The results showed that injection of the PMSG hormone as a superovulation agent before mating is able to increasing piglet birth weight but not able to increase the litter size significantly. Increased productivity of sows through superovulation method is to extend the production period of the sow, especially sows with a number of birth five or more times without being replace by new gilt.